Identification and distribution of arbuscular mycorrhizal spores in selected plant roots and their surrounding soil - Tiang, Bi Ren. (Universiti Malaysia Sarawak (UNIMAS), 2015)
Arbuscular mycorrhizas fungi (AMF) possess great potential in ecosystem especially in agricultural system as they can contribute towards the sustainability of the system. AMF have the ability to increase nutrient uptake, alleviate environmental stresses, and potential as bio-fertilizer. Thus, the aim of this project was to isolate, characterize and identify morphologically types of AMF present in selected plants sampled around Kota Samarahan which consists of Cassava, Carica papaya, Cymbopogon, and Pandanus ammyllifolius, quantification of AMF spores, and analysis of soil physicochemical properties towards colonization of AMF. Isolation process of AMF spores was carried out using wet sieving and decanting method and spores were characterized morphologically. From result obtained, genera of AMF isolated consisted of Acaulospora, Funneliformis, Glomus, and Rhizophagus whereby genus Glomus was found dominant among all plant samples. It also showed that soil texture and pH affect the colonization rate of AMF. Cassava recorded the highest colonization rate of AMF with 20% whereas Cymbopogon recorded lowest AMF colonization rate of 10% only. From this study, AMF spores were successfully isolated from different plant roots and characterized morphologically. Soil texture and soil pH were found to affect the colonization rate of AMF in plants.